Probabilistic-Input, Noisy Conjunctive Models for Cognitive Diagnosis - Zhan, Peida; Wang, Wen-Chung; Jiao, Hong; Bian, Yufang (Frontiers in Psychology, 2018)
Existing cognitive diagnosis models conceptualize attribute mastery status discretely as either mastery or nonmastery. This study proposes a different conceptualization of attribute mastery as a probabilistic concept, i.e., the probability of mastering a specific attribute for a person, and developing a probabilistic-input, noisy conjunctive (PINC) model, in which the probability of mastering an attribute for a person is a parameter to be estimated from data. And a higher-order version of the PINC model is used to consider the associations among attributes. The results of simulation studies revealed a good parameter recovery for the new models using the Bayesian method. The Examination for the Certificate of Proficiency in English (ECPE) data set was analyzed to illustrate the implications and applications of the proposed models. The results indicated that PINC models had better model-data fit, smaller item parameter estimates, and more refined estimates of attribute mastery.